The leadership gap what gets between you and your greatness - Lolly Daskal (New York Portfolio/Penguin, 2017)
"Inc. magazine's most popular writer, executive coach Lolly Daskal explains how anyone can recognize and leverage the leadership gaps that stand in the way of greatness. When successful people begin to feel uncertain or challenged at work, the one thing they want to know most is why things are going wrong after they have gone right for so long. In The Leadership Gap, Lolly Daskal reveals the consequences highly driven, overachieving leaders face when they continue to rely on a skill set that has always worked for them, even when it is no longer effective. Over decades of advising and inspiring the most prominent chief executives in the world, Daskal has discerned that leaders fall into one of seven categories -- The Rebel, The Explorer, The Truth Teller, The Hero, The Inventor, The Navigator, and The Knight-- and have risen to their position relying on a specific set of values and traits. However, every leader reaches a point when their effectiveness is compromised by the gap hidden in those traits -- intuition becomes manipulation, for instance, or integrity becomes corruption. Based on a mix of modern philosophy, science, and her own vast well of business experience, Daskal offers a breakthrough perspective on leadership -- a new system for rethinking everything you know to reveal the path to becoming the kind of leader you truly want to be. In The Leadership Gap, Lolly Daskal not only confirms her stature as an exceptional business mind, but also reveals the insights and observations of one of our most important leadership experts -- a businesswoman known for providing trusted advice, actionable solutions, and provocative ideas to the world's top executives"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Leadership